Lung cancer screening patient–provider discussion: Where do we stand and what are the associated factors?. (May 2019) - Chalian, Hamid; Khoshpouri, Pegah; Iranmanesh, Arya M; Mammarappallil, Joseph G; Assari, Shervin
Objective: The primary objective of this study was to estimate the percentage of individuals possibly eligible for lung cancer screening that report having discussed screening with a health care provider. The secondary objective was to investigate the associated factors of having patient–provider lung cancer screening discussion. Methods: Data from the Health Information National Trends Survey 2017 were used ( n = 3217). Lung cancer screening eligibility was based on the criteria utilized by the Centers for Medicare and Medicaid Services. Gender, race, educational attainment, health insurance coverage, and usual source of health care were covariates. Current or former smokers ages 55–77 ( n = 706) were considered potentially eligible for lung cancer screening (dependent variable). Results: Only 12.24% of individuals potentially eligible for lung cancer screening report prior discussion regarding lung cancer screening with a health care provider. Being eligible for lung cancer screening based on Centers for Medicare and Medicaid Services eligibility criteria was positively associated with the odds of a patient–provider lung cancer screening discussion (odds ratio = 3.95, 95% confidence interval = 2.48–6.30). Unlike gender, race, education, or insurance coverage, a usual source of health care was positively associated with a patient–provider screening discussion (odds ratio = 2.48, 95% confidence interval = 1.31–4.70). Conclusion: Individuals potentially eligible for lung cancer screening are more likely to have screening discussions with a health care provider. Having a usual source of health care may increase the odds of such a discussion, while patients are not discriminated based on race, gender, education, and insurance coverage. However, the relatively low rate (12.24%) of reported patient–provider lung cancer screening discussion indicates that significant barriers still remain.